2019
DOI: 10.1111/acps.13061
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mechanical restraint of psychiatric inpatients by applying machine learning on electronic health data

Abstract: Objective Mechanical restraint (MR) is used to prevent patients from harming themselves or others during inpatient treatment. The objective of this study was to investigate whether incident MR occurring in the first 3 days following admission could be predicted based on analysis of electronic health data available after the first hour of admission. Methods The dataset consisted of clinical notes from electronic health records from the Central Denmark Region and data from the Danish Health Registers from patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…Treatment issues such as adherence or misuse are also depicted (6 cases) [ 56 , 72 , 74 , 81 , 101 , 103 ]. Only 1 study on mechanical restraints [ 90 ] and 1 on cognitive troubles [ 97 ] were found. A total of 8 studies were transnosographic [ 59 , 67 - 71 , 73 , 76 ]: 6 met the CEGS N-GRID 2016 Center of Excellence in Genomic Science Neuropsychiatric-Genome-Scale and Research Domain Criteria (RDoC) Individualized Domains 2016 Shared Task in Clinical NLP criteria, which will be developed further in our results.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment issues such as adherence or misuse are also depicted (6 cases) [ 56 , 72 , 74 , 81 , 101 , 103 ]. Only 1 study on mechanical restraints [ 90 ] and 1 on cognitive troubles [ 97 ] were found. A total of 8 studies were transnosographic [ 59 , 67 - 71 , 73 , 76 ]: 6 met the CEGS N-GRID 2016 Center of Excellence in Genomic Science Neuropsychiatric-Genome-Scale and Research Domain Criteria (RDoC) Individualized Domains 2016 Shared Task in Clinical NLP criteria, which will be developed further in our results.…”
Section: Resultsmentioning
confidence: 99%
“…inform teaching strategies and education policies), in political psychology (in which large-scale surveys aimed at informing prediction of voting behavior are periodically conducted and many efforts are devoted to developing text models detecting toxic or misleading political contents), and in several domains of clinical research (in which predictive models are used for purposes ranging from causal modeling of psychiatric diagnoses to predicting patients' risk of being subjected to mechanical restraint; see Danielsen et al, 2019). Other clinical fields have fewer readily available data sets but also have high potential.…”
Section: Clear Practical Implicationsmentioning
confidence: 99%
“…Predicting real-life outcomes is also an important goal in educational psychology (where understanding the factors that impact educational achievement can directly inform teaching strategies and education policies), in political psychology (where large-scale surveys aimed at informing prediction of voting behavior are periodically conducted, and many efforts are devoted to developing text models detecting toxic or misleading political contents), and in several domains of clinical research (where predictive models are used for purposes ranging from causal modeling of psychiatric diagnoses, to predicting patients' risk of being subjected to mechanical restraint, see Danielsen, Fenger, Østergaard, Nielbo, & Mors, 2019). Other clinical fields have fewer readily available datasets, but also have high potential.…”
Section: Clear Practical Implicationsmentioning
confidence: 99%